Targeted Metabolomics of Tityus Scorpion Venoms: Unveiling Small-Molecule Components - Dias, Nathalia Baptista; de Souza, Bibiana Monson [UNESP]; Barroso, Geovanny [UNESP]; Leiva, Javier Ortiz; Paula, Gabriela Mendonça [UNESP]; Chalkidis, Hipócrates M.; Dorce, Valquíria Abrão Coronado; Malaspina, Osmar [UNESP]; Palma, Mario Sergio [UNESP] (American Chemical Society (ACS), 2025)
Scorpion venoms consist of proteins, peptides, and various low molecular weight (LMW) organic compounds, which act as toxins. Despite their potential significance, these compounds in scorpion venoms have been little investigated and their full range has not been well characterized. In this work, a targeted metabolomic approach was used in combination with an HPLC-QTOF-MS methodology to create a library of 55 LMW standard compounds, for the analysis of venoms from three Tityus species scorpions. This strategy enabled reliable identification of 45 compounds, including 20 amino acids, 4 organic acids, 12 biogenic amines, 6 nitrogenated bases and derivatives, 2 β-carboline-derived alkaloids, and 1 amphetamine. Most of the compounds identified were neurotransmitters and/or neurotoxins, while others can act as homeostasis disruptors or affect the diffusion of venom through the bodies of victims. Therefore, the LMW organic compounds in scorpion venoms play roles in the killing or paralyzing of prey, as well as in defense against large predators.